2018
DOI: 10.3126/jcmsn.v14i4.20243
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid dysfunction among patients with diabetes mellitus in Kathmandu

Abstract: Background: This study was conducted with the objective of studying thyroid dysfunction in patients with diabetes mellitus. Materials and Methods: A total 100 patients consisting of 40 males and 60 females diagnosed as diabetes were included in the study. Laboratory values of different thyroid parameters were taken. Results: Among the participants 60% were female and 40% were male. Age ranged from 17 to 88 years with mean being 55.73 ± 1.62 years. Presence of thyroid dysfunction was found in 35% of the cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(5 reference statements)
1
0
0
Order By: Relevance
“…Different studies found prevalece of hypothroidism (26.5%), (20%), (10.7%), (14%) and (18%) which is similar to our sudy. 4 , 6 - 9 The present study also documented 14.06% of clinical hypothyroidism in T2DM patients which was a similar finding to the study (13.9%). 2 , 10 Our study found a high prevalence of subclinical hypothyroidism in female T2DM patients than in male T2DM patients.…”
Section: Discussionsupporting
confidence: 91%
“…Different studies found prevalece of hypothroidism (26.5%), (20%), (10.7%), (14%) and (18%) which is similar to our sudy. 4 , 6 - 9 The present study also documented 14.06% of clinical hypothyroidism in T2DM patients which was a similar finding to the study (13.9%). 2 , 10 Our study found a high prevalence of subclinical hypothyroidism in female T2DM patients than in male T2DM patients.…”
Section: Discussionsupporting
confidence: 91%